The Influence of Insurance Market on the Economic Development of Ukraine - Rybalchenko, Liudmyla (Journal of Finance and Financial Law, 2018)
The level of economic development and the economic growth rates in Ukraine are very uneven. On the basement of production function were analyzed the factors of economic development in Ukraine. The influence of the level of the insurance development on its economic growth was considered.